PENGEMBANGAN MEDIA PEMBELAJARAN BERBASIS TELEGRAM PADA KELAS IV SEKOLAH DASAR SWASTA LKIA PONTIANAK SELATAN - Nofrando Firman Saputra; Hery Kresnadi; Suparjan Suparjan (Jurnal Pendidikan dan Pembelajaran Khatulistiwa (JPPK), 2021)
AbstractThe purpose of this article was to develop a telegram-based learning media on get to knowthe traditional house of nusantara in the fourth grade of SDS LKIA South Pontianak. Thistype of research is a development research using the ADDIE model with the steps ofanalysis, design, development, implementation, evaluation. Quantitative data wereobtained from the product results by the validator as well as filling in the practicality dataof learning media by teachers and students. Qualitative data were obtained fromsuggestions and notes by validators, teachers, and students. The research instrument wasin the form of interview guidelines and questionnaires. The level of media validity is basedon the results of the assessment by design experts, and material experts, while thepracticality level of learning media is based on the learning outcomes of students andteachers of class IV SD LKIA South Pontianak. The results of the validation of learningmedia design experts obtained an average of 4.9 "very valid". The results of the validationof learning media materials obtained an average of 4.7 "very valid". The results of thepracticality of learning media by students get an average of 3.40 "very practical". Theresults of the practicality assessment of learning media by teachers obtained an averageof 3.57 "very practical".Keywords: leraning media, telegram